On Improving Public Expenditure Policies for the Poor : Major Informational Requirements - Chalk, Nigel; Ahmad, Ehtisham (Washington, D.C. : International Monetary Fund, 1993)
An improvement in the quality of public expenditures is needed in many countries, given binding macroeconomic and fiscal constraints, and poverty reduction and distributional objectives. This process involves a reassessment of methodology used for this purpose by countries and international agencies, and the data needed for improved decision making. This paper reviews methods that might be used by international agencies, such as the Fund and the Bank, jointly with a survey of data currently available, required improvements in the data currently available, and required improvements in the information base. The scope for improvements in governments' expenditure policy making is also considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet